Development of a methodology for measuring the quality of statutory social workers' complex decision-making. - Angela Lilly; Tim Rakow; Jill Manthorpe; Benjamin Gardner (PLoS ONE)
Registered social workers in English Local Authorities are required to have an expertise in the complex decision-making needed to promote well-being when an adult's own judgement about their well-being and wishes about how to promote it might, in the circumstances, put their well-being at risk. Such circumstances are complex partly because core professional values - promoting autonomy and protecting from harm - can come into conflict. Given the consequential nature of social workers' decisions, it is essential to be able to evaluate the quality of social workers' decision-making. In this paper, we set out the systematic development, in collaboration with expert social workers, of a bespoke methodology to measure decision-making quality and investigate underpinning cognitive processes. Central to our methodology was social workers' consideration of key legal principles. First, we reviewed the research literature to identify existing measurement schemes aspects of which might be suitable for incorporating into our methodology. No existing measurement schemes were found, but we identified a factorial survey vignette-based scheme which seemed promising as the basis for our own methodology. Second, by reviewing statute and case law, we identified 40 key legal principles which social workers should consider in their decision-making. Next, based on these principles, we developed four hypothetical case vignettes to activate decision-making. Finally, we developed four scoring templates, one for each vignette, setting out exemplar judgements and decisions against which practitioners' judgements and decisions could be compared and scored. Our new methodology provides a means of assessing the quality of social workers' decision-making and, as prior- and post-intervention quality can be measured, has the potential to generate evidence of the impact of policy and practice interventions on decision-making.